The end of Roe v. Wade: implications for Women’s mental health and care - Londoño Tobón, Amalia; McNicholas, Eileen; Clare, Camille A.; Ireland, Luu D.; Payne, Jennifer L.; Moore Simas, Tiffany A.; Scott, Rachel K.; Becker, Madeleine; Byatt, Nancy (Frontiers in Psychiatry, 2023)
The Supreme Court decision in Dobbs v. Jackson in June 2022 reversed precedent which had previously protected abortion prior to fetal viability as a universal right within the United States. This decision almost immediately led to abortion restrictions across 25 states. The resulting lack of access to abortion care for millions of pregnant people will have profound physical and mental health consequences, the full effects of which will not be realized for years to come. Approximately 1 in 5 women access abortions in the U.S. each year. These women are diverse and represent all American groups. The Supreme court decision, however, will affect populations that have and continue to be marginalized the most. Forcing pregnant individuals to carry unwanted pregnancies worsens health outcomes and mortality risk for both the perinatal individual and the offspring. The US has one of the highest maternal mortality rates in the developed world and this rate is projected to increase with abortion bans. Abortion policies also interfere with appropriate medical care of pregnant people leading to less safe pregnancies for all. Beyond the physical morbidity, the psychological sequelae of carrying a forced pregnancy to term will lead to an even greater burden of maternal mental illness, exacerbating the already existing maternal mental health crisis. This perspective piece reviews the current evidence of abortion denial on women’s mental health and care. Based on the current evidence, we discuss the clinical, educational, societal, research and policy implications of the Dobbs v. Jackson Supreme Court decision